Relationship between Movement Speed and Accuracy during Eye Gaze Control of Computer Cursor - Miniotas, D.; Laurutis, V. (Elektronika ir Elektrotechnika, 2000)
An experiment is described comparing the performance of an eye tracker and a mouse in a simple pointing task. Subjects had to make rapid and accurate horizontal movements to targets that were vertical ribbons located at various distances from the cursor’s starting position. The dwell-time protocol was used for the eye tracker to make selections. Movement times were shorter for the mouse than for the eye tracker. Fitts’ Law model was shown to predict movement times using both interaction techniques equally well. The model is thus seen to be a potential contributor to design of modern multimodal human-computer interfaces.